Market potential and welfare : evidence from the Iberian Peninsula - Pires, Armando José Garcia (2018)
We present a methodology to quantify market potential in the context of an economic geography model. The model is then applied to the NUTS 2 regions of Portugal and Spain. Some results can be pointed out. First, the Iberian Peninsula presents a clear centre-periphery pattern. The market potential pike is situated in the region of Madrid, followed very closely by Catalu˜na and Pais Vasco. Also all Portuguese regions are at the bottom of the market potential rank, i.e.: Portugal is at the periphery of Spain. Second, the regional welfare index confirms market potential results. There is therefore a direct correlation between market potential and regional welfare. Third, a scenario of complete integration between the Portuguese and the Spanish economy is favourable to the most laggard regions. On the contrary, the most advanced regions of each country loose a little. However, ‘lock-in’ effects allow the most central regions to continue in the forefront of development and welfare.